Two sermons preached before the Twenty-eighth Congregational Society in Boston on the 14th and 21st of November, 1852: on leaving their old and entering a new place of worship - Parker, Theodore (Crosby, Nichols, & Co., 1853)
Some account of my ministry -- Of the position and duty of a minister.